Legal Responsibility for Misuse of Restricted Over-The-Counter Medicine Sold by Small Traders - Atrianta Dea Puspita; Yovita Arie Mangesti (Activa Yuris: Jurnal Hukum, 2024)
The purpose of this legal research is to find out about the applications of doctors who perform telemedicine services and to find out the legal protection for doctors who perform telemedicine services. By using normative legal research method, this research uses statute approach and conceptual approach. Based on this research, a conclusion is obtained that refers to Law Number 36 of 2009 concerning Health, Minister of Health Regulation Number 20 of 2019 concerning the Implementation of Telemedicine Services Between Health Service Facilities, and Law Number 29 of 20004 concerning Medical Practice. However, these regulations have not provided legal protection for doctors who perform telemedicine services both in statutory provisions and the medical code of ethics. Legal protection should be provided through a new law on doctors who perform remote virtual services (telemedicine) which contains telemedicine authority so that there are limits to the authority of doctors to perform telemedicine services.